Workshop dan Edukasi Pemanfaatan Herbal sebagai Upaya Peningkatan Kesehatan Keluarga pada Anggota PKK: Workshop and Education on Herbal Utilization to Enhance Family Health for PKK Members - Ebtavanny, Tamara Gusti; Hariadini, Ayuk Lawuningtyas; Firdaus, Favian Rafif; Achmad, Anisyah; Amalia, Thia; Nabilah, Varna Amalia; Fauzan, Evan; Azis, Umar Abdul; Wibowo, Andriani Abigail (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Family Welfare Empowerment (PKK) is a community group dedicated to fostering family and societal well-being, with health being one of its key focus areas. PKK members are pivotal in enhancing family immunity, particularly during heightened risk from bacterial, viral, and other infections. The community's preference for traditional medicine, which has been empirically proven to be safe and effective, such as *Andrographis paniculata* (sambiloto) and *Curcuma longa L.* (turmeric), serves as a viable solution for boosting family immunity. This program aimed to provide education and workshops to 50 PKK members in Kendalpayak Village through education sessions, pre-and post-tests, a herbal drink preparation workshop, and follow-up consultations. The education covered topics on the immune system, the definition and application of traditional medicine, and the rational use of herbal remedies. The program results revealed a significant improvement in participants' knowledge, with average pre-test scores of 81.71 rising to 93.90 in post-tests, reflecting a 12.19% increase. Furthermore, the proportion of participants with "Good" knowledge levels rose from 75.61% to 92.68%. The workshop successfully trained participants in practical herbal preparation by demonstrating the production of three types of immune-boosting herbal drinks, supported by educational materials that had obtained intellectual property rights. Participant satisfaction with the program was notably high, averaging 96.06%. These results demonstrate the program's tangible benefits in enhancing community knowledge and skills, potentially supporting family health and well-being in the future.